Level of IL-6, TNF, and IL-1β and age-related diseases: a systematic review and meta-analysis - Tylutka, Anna; Walas, Łukasz; Zembron-Lacny, Agnieszka (Frontiers in Immunology, 2024)
Chronic low-grade inflammation is an important aspect of morbidity and mortality in older adults.The level of circulating pro-inflammatory cytokines (interleukin (IL)-6, tumor necrosis factor (TNF) or IL-1β) is a risk factor in cardiovascular and neurodegenerative diseases and is also associated with sarcopenia and frailties. The objective of this study was to assess each cytokine: IL-6, TNF, and IL-1β separately in the elderly with comorbidities against controls without diseases according to the data published in the available literature. The electronic bibliographic PubMed database was systematically searched to select all the relevant studies published up to July 2023.The total number of the subjects involved in the meta-analysis included patients with diseases (n=8154) and controls (n=33967). The overall concentration of IL-6 was found to be higher in patients with diseases compared to controls and the difference was statistically significant, with a pvalue of <0.001 (SMD, 0.16; 95% CI, 0.12-0.19). The heterogeneity was considerable with Q = 109.97 (P <0.0001) and I 2 = 79.2%. The potential diagnostic usefulness of IL-6 was confirmed by odds ratio (OR) analysis (OR: 1.03, 95% CI (1.01; 1.05), p=0.0029). The concentration of both TNF and IL-1β was elevated in the control group compared to patients and amounted to SMD -0.03; 95% CI, -0.09-0.02, p-value 0.533 and SMD-0.29; 95% CI, -0.47–0.12; p = 0.001, respectively.For TNF, however, the difference was statistically insignificant. Therefore, IL-6, unlike TNF and IL-1β, could be a useful and convenient marker of peripheral inflammation in older adults with various comorbidities.